2020
DOI: 10.7759/cureus.8816
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Practice and Determinants of Diabetes Self-Care in Primary Health Care in Jeddah City, Saudi Arabia

Abstract: Objective To assess the level and determinants of practice in diabetes self-management at primary health care centers (PHCCs) and to analyze the association of self-management with the level of glycemic control. Method A cross-sectional study was conducted among patients with type 1 and type 2 diabetes, aged ≥ 17 years, and being followed at PHCCs in Jeddah, Saudi Arabia, from December 1, 2019, to December 30, 2019. A multistage cluster sampling technique was used to select 350… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 30 publications
2
17
1
Order By: Relevance
“…Others reported similar poor dietary adherence and foot care among patients with T2DM. 4 , 12 , 18 , 29 , 30 Interestingly, participants’ adherence to a specific diet was higher than that of a general diet, which others reported. 18 , 29 Consistently, Bawadi et al reported that diabetic patients in Jordan failed to achieve the recommended dietary guidelines for Arabs.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Others reported similar poor dietary adherence and foot care among patients with T2DM. 4 , 12 , 18 , 29 , 30 Interestingly, participants’ adherence to a specific diet was higher than that of a general diet, which others reported. 18 , 29 Consistently, Bawadi et al reported that diabetic patients in Jordan failed to achieve the recommended dietary guidelines for Arabs.…”
Section: Discussionmentioning
confidence: 93%
“…Most study participants reported unsatisfactory compliance to diabetes self-care behaviors, less than four days/week on average, consistent with the findings of previous Jordanian 16 , 18 , 29 and international studies. 11 , 12 , 21 , 30 , 31 In contrast, Qteishat & Ghananim (2015) reported high compliance to diabetes self-care activities using the same measurement tool. However, their study was conducted in different settings, in west-central Jordan, and with smaller sample size.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ability of DM clients in managing good self-care can control blood sugar. Controlled blood sugar will reduce the risk of disease complications (AlQahtani et al, 2020;Helou et al, 2016).…”
Section: Discussionmentioning
confidence: 99%